2018
DOI: 10.15171/jpid.2015.007
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Reproducibility of Linear Measurements of Alveolar Ridges Using Cone-beam CT Made by Radiologists and Periodontists

Abstract: Background and aims. The aim of this study was to evaluate the intra- and inter-examiner reliability and reproducibility of linear measurements on cone-beam computed tomography (CBCT) images made by calibrated radiologists and periodontists. Materials and methods. The alveolar ridge dimensions were measured on selected CBCT images by two calibrated radiologists and two periodontists. Intra- and inter-examiner reliability was evaluated by intra-rater and intra-class correlation coefficients (ICCs). Results. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…Also, the inter-examiner measurement error for the height of the edentulous ridge was 0.42 mm. The values observed from this study showed almost perfect agreement between the observers when compared to the findings from the study by Safi et al [2]. They assessed the reliability of linear measurements of the alveolar ridges made by radiologists and periodontists on 23 CBCT images and stated that there was almost perfect agreement between the observers.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Also, the inter-examiner measurement error for the height of the edentulous ridge was 0.42 mm. The values observed from this study showed almost perfect agreement between the observers when compared to the findings from the study by Safi et al [2]. They assessed the reliability of linear measurements of the alveolar ridges made by radiologists and periodontists on 23 CBCT images and stated that there was almost perfect agreement between the observers.…”
Section: Discussionsupporting
confidence: 77%
“…These include the evaluation of edentulous sites for implant placement, extent and size of cysts, tumors that affect the jaws, measuring airway spaces, and cephalometric analysis. CBCT software enables the operator to measure the linear and curvilinear dimensions of structures with a high degree of reliability [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation